Treatment for non-small-cell lung cancer and circulating tumor cells - Mason, Joel (Lung Cancer Manag, 2017)
Surgery is the main curative therapy for patients with localized non-small-cell lung cancer while radiotherapy (RT), alone or with concurrent platinum-based chemotherapy, remains the primary curative modality for locoregionally advanced non-small-cell lung cancer. The risk of distant metastasis is high after curative-intent treatment, largely attributable to the presence of undetected micrometastases, but which could also be related to treatment-related increases in circulating tumor cells (CTCs). CTC mobilization by RT or systemic therapies might either reflect efficient tumor destruction with improved prognosis, or might promote metastasis and thus represent a potential therapeutic target. RT may induce prometastatic biological alterations in CTC at the cellular level, which are detectable by ‘liquid biopsies’, though their rarity represents a major challenge. Improved methods of isolation and ex vivo propagation will be essential for the future of CTC research.